Stress Testing and Bank Lending - Shapiro, Joel; Zeng, Jing (Review of Financial Studies, 2024)
Abstract Stress tests convey information about the strictness of future tests, creating incentives for banks to alter their future lending behavior. Regulators recognize and use this influence: they may conduct softer stress tests to encourage lending or tougher stress tests to reduce risk-taking. This information management can lead to inefficiencies when (a) the test loses credibility or (b) the test becomes self-fulfilling. In addition, banks may distort their lending behavior in anticipation of the stress test design, leading to further surplus losses. The analysis applies to banking supervision and regulation more broadly.